Speech-language pathologists' perspectives on cognitive communication assessment during post-traumatic amnesia. (28th July 2016) - Steel, Joanne; Ferguson, Alison; Spencer, Elizabeth; Togher, Leanne
Abstract: Primary objective : There have been few reports of the approaches taken by speech-language pathologists (SLPs) when assessing cognitive communication (CC) during post-traumatic amnesia (PTA) after TBI. This study sought to understand SLPs' rationales for CC assessment during PTA and to examine their perspectives on assessment methods during the early recovery period. Methods and procedures : In this qualitative study, 10 SLPs participated in semi-structured face-to-face or telephone interviews about their rationales and methods for CC assessment during PTA and early recovery. Content analysis was conducted using NVivo software to identify key categories. Main outcome and results : SLPs reported their reasons for CC assessment as including: (1) Documenting changes and monitoring progress, (2) Feedback to team, family and patient, (3) Diagnosis of communication disorder, (4) Planning and (5) Prognosis. They described conducting ongoing, informal assessment and monitoring of CC, using a combination of standardized and non-standardized measures during PTA, and commenced formal testing after PTA resolution to formulate a baseline level of communication function. Conclusions : The current study highlighted the importance that SLPs placed on an individualized approach in CC assessment. Findings provided insight into the process of assessment of CC during PTA and the early stage of recovery after TBI.